The Midwife’s Tale: Old Wisdom and a New Challenge to the Control of Reproduction - Martin, Dianne L. (Columbia Journal of Gender and Law, 1992)
Reproductive rights for women remain elusive and contested. All over the world poor women continue to be denied access to even basic health care and information. Privileged women also face the dehumanizing effects of a fetal rights campaign which successfully “fetishizes the fetus,”‘ as women’s demands for reproductive choice2 are balanced against the separately constituted interests of fathers and the state in the production and protection of the ultimate innocent third party-the fetus.